(untitled) (Research, Society and Development, 2021)
Introduction: Urinary Incontinence (UI) is any involuntary loss of urine, according to the International Continence Society (ICS). Objectives: To analyze the prevalence of signs and symptoms of stress urinary incontinence in women who practice weight training. Methodology: Cross-sectional study of a quantitative type, carried out online by 195 women who practiced weight training, of which only 52 were included in the present study, they answered a questionnaire to which they collected information from their personal lives for analysis of criteria and then the ICIQ-SF for UI analysis with regard to frequency, quantity, interference in personal life and when to lose urine. Results: There were reports of urinary losses in 19.24% of the volunteers. The mean age was 27.11 years (SD ± 5.61), 21.15% of those who presented urinary loss reported an impact from severe to very severe and 73.08% said they had no impact. 11.54% of women presented complaints of activities that require effort. Urinary loss was greater in those who performed more than one type of physical activity, occurring in 6 out of 10 women who had incontinence. Conclusion: It could be concluded that, despite the limitation in the sample, it was observed that the signs and symptoms of urinary incontinence were present in women who practice weight training and the impact that the pathology causes on their quality of life.